COUNSELING PROGRAM TO ENHANCE SELF-CONTROL OF INMATES WITH PSYCHOLOGICAL DISORDERS IN CLASS IIB BREBES CORRECTIONAL INSTITUTION - Naily Fauziah Ayyasi; Budi Priyatmono (Journal of Management Small and Medium Enterprises (SME's))
This study aims to analyze the effectiveness of a counseling program in improving the self-control of prisoners with psychological disorders at Brebes Class IIB Correctional Institution. Prisoners often experience psychological disorders due to social isolation, overcapacity, and the pressures of life in prison, which have a negative impact on their self-control. The counseling program implemented aims to help prisoners develop self-control through a Cognitive Behavioral Therapy (CBT) approach and mental health screening using the Self-Reporting Questionnaire (SRQ-29). The results indicated that counseling significantly improved the psychological condition of prisoners, with positive behavioral changes, increased self-discipline, emotional management, and healthy habits. The success of this program is measured through five main aspects: behavior change, mental health, problem-solving, self-discipline, and healthy habits. For optimal effectiveness, increasing the frequency of counseling, training prison officers, and providing better counseling facilities are recommended.